Proces decyzyjny funduszy typu venture capital - Grzech, Aleksandra (Decision-making Process of Venture Capital Investors, 2008)
"Venture capital investors seek companies, whose value in the period of investment will grow considerably,exceeding the originally invested amount. They focus on investments with a higher level ofrisk. Finding ‘the star’ is not simple, therefore systematizing the action of the decision-making processis necessary in order to appoint ‘the star’. This process consists of a few stages. Firstly the mainpurpose, which will determine actions taken in further phases, should be set. Then follows selectionof proposed project to collect a set of variants. The next step, which consist of formulating assessment'scriteria and judging companies, requires working out quantitative characteristics and mathematicalmodels. As a result, assessments of individual variants will be received. Taking a definitivedecision is based on outcomes of the assessment."
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 198-206